Weak Scale Supersymmetry From Superfields to Scattering Events - Baer, Howard (Cambridge University Press, 2007)
Supersymmetric models of particle physics predict new superpartner matter states for each particle in the Standard Model. These superpartners will have wide ranging implications, from cosmology to observations at high energy accelerators, such as CERN's LHC. In this 2006 text, the authors develop the basic concepts of supersymmetry and show how it can be incorporated into a theoretical framework for describing unified theories of elementary particles. They develop the technical tools of supersymmetry using four-component spinor notation familiar to high energy experimentalists and phenomenologists. The text takes the reader from an abstract formalism to a straightforward recipe for writing supersymmetric gauge theories of particle physics, and ultimately to the calculations necessary for practical applications at colliders and in cosmology. This is a comprehensive, practical and accessible introduction to supersymmetry for experimental and phenomenological particle physicists and graduate students. It has been reissued as an Open Access publication.